Application of failure detection methods to detect information attacks on the control system - Margun, A.A.; Iureva, R.A.; Kolesnikova, D.V. (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2024)
The problem of ensuring the security of control systems is an important and urgent problem. It consists of eliminating the impact of failures and attacks on control objects and the environment, etc. Prevention of critical failures is important. The purpose of this study is to analyze the similarities between the consequences of attacks on complex technical systems and failures of these systems. In the course of the work, a hypothesis about the similarity of the impact of failures and information attacks on a complex technical system is presented. Both information attacks and failures cause anomalous dynamics of the control object. Analysis of the deviation of the dynamics of the control object from the normal mode of operation will allow us to detect and isolate information attacks and failures. The paper examines the influence of information attacks on the dynamics of automatic control systems. Comparison of abnormal dynamics of control objects during attacks and device failures is carried out. The similarity of the consequences of information attacks and failures of the control system are analyzed, a method for identifying attacks based on the methods developed for detecting failures is developed. Computer modeling of the influence of information attacks and failures on the control system of a DC motor has been carried out. The simulation results allow making a conclusion about the applicability of the failure detection algorithms for detecting attacks. It is shown that failures and information attacks can lead to dangerous consequences for the control system. It seems relevant to study the intersection of the field of information security and failure detection.